Impact of toxic leadership on nurses' motivation, job satisfaction, productivity, and turnover intentions - Solehudin, Solehudin; Syabanasyah, Inas (Journal of Health Science and Medical Therapy, 2024)
Toxic leadership refers to a style of leadership characterized by behaviors that harm, exploit, and undermine the well-being of employees and the overall organizational culture. Leaders who exhibit toxic behaviors often create a detrimental work environment that affects not only the morale and productivity of their team but also the long-term success of the organization. The purpose of this study was to determine the influence of toxic leadership on motivation, job satisfaction, productivity and turnover intention of nurses. This study uses correlation analysis with a cross-sectional design. The population in this study were nurses with a sample size of 480 responden based on the convenience sampling technique. Statistical analysis using multiple linear regression. The results of the study showed that the influence of toxic leadership on motivation, job satisfaction, productivity and turnover intention was p value 0.001. standard estimate coefficient of motivation and job satisfaction variables is a value of 1,000. The conclusion of this study is toxic leadership has a negative impact on nurse motivation by reducing intrinsic motivation. When job satisfaction decreases due to toxic leadership, nurses are more likely to consider leaving their jobs.